RANCANG BANGUN SISTEM SATELIT BUATAN BERBASIS ESP32 DENGAN FITUR KOMUNIKASI MENGGUNAKAN MODUL GSM SIM800L - Jati Kinsela Brajamusti; Cindy Kaillah Nurjanah (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2023)
Satellites are objects orbiting in space designed to perform specific tasks such as observation, communication, and navigation on Earth. Satellites can send and receive signals to communicate, take pictures of the earth, and monitor the weather. SMS (Short Message Service) based satellite connectivity with ESP32 and SIM800L provides a more cost-effective data transmission solution. ESP32 acts as the satellite's brain, controlling and collecting various sensors to measure the environment. The SIM800L module, on the other hand, provides cellular connectivity and enables data transfer over cellular networks. The purpose of this technology cable is to reduce the complexity and cost of satellite development and open new opportunities for research in satellite communications technology.